Anti-collision system for indoors quadcopter navigation using fuzzy controllers and range sensors (Revista de Investigaciones Universidad del Quindío, 2016)
This project presents the results of introducing a speed control by using ultrasound and accelerometer sensors to detect objects associated to a fuzzy controller to prevent collisions in enclosed spaces. By implementing this anticollision model, indoor navigation of aerial robots becomes safer.
Keywords: range sensors; spatial navigation; obstacle avoidance; signal processing; sonar; Quadrotor; fuzzy logic; fuzzy controller